Impact of Advanced Radar Technology on Traffic Volume and Speed Analysis in Urban Expressways at Klang Valley - Syed Khairi Syed Abbas,; Amin Nurliyana Mat Yusoff,; Jezan Md Diah,; Muhammad Akram Adnan,; Adi Yazid Rosli, (International Journal of Integrated Engineering, 2025)
Traffic congestion on urban expressways significantly affects individual productivity by impacting drivers' time on the road. Traffic performance, especially during peak hours, is influenced by the simultaneous presence of different vehicle classes. While research on the relationship between traffic volume and speed in congested areas is well-established, contemporary methods and advanced radar technologies like Speedlane Pro™ Counter Classifier offer new insights. This advanced radar technology provides multiple options for gathering accurate traffic data, including traffic volume and vehicle speed, which are crucial for reliable studies. This research focuses on the Klang Valley Expressway in Malaysia, aiming to enhance the understanding of traffic congestion and its correlation with vehicle speed and volume. By calculating the Level of Service (LOS) and examining these parameters, the study aims to provide valuable insights for traffic management and planning. The findings will benefit communities concerned with traffic congestion, offering a basis for improving expressway efficiency and reducing the negative impacts of traffic delays.